2005
DOI: 10.1111/j.1365-2621.2005.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooking methods on chlorophylls, pheophytins and colour of selected green vegetables

Abstract: The effect of microwave and conventional cooking methods on chlorophyll pigments and colour properties of squash, green beans, peas, leek, broccoli and spinach were studied, by HPLC and colorimetry, respectively. In five of six vegetables, chlorophyll a was found more heat resistant compared with chlorophyll b, except in peas. Chlorophylls in peas were retained to the 80-90%, the highest in all vegetables evaluated. Chlorophylls were retained to 19-100%, depending on the vegetable type and cooking method. Pheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
85
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 31 publications
15
85
0
8
Order By: Relevance
“…The degree of greenness, due to chlorophyll content, is important in determining the final quality of green vegetables (Nisha et al, 2004). It was also reported that chlorophyll and its derivatives exerted beneficial effects such as anticarcinogenic and antimutagenic activities (Turkmen et al, 2006). Green vegetables exhibit poor color quality and decreased chlorophyll content as compared with the raw material after thermally processed (Adebooye et al, 2008;Turkmen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of greenness, due to chlorophyll content, is important in determining the final quality of green vegetables (Nisha et al, 2004). It was also reported that chlorophyll and its derivatives exerted beneficial effects such as anticarcinogenic and antimutagenic activities (Turkmen et al, 2006). Green vegetables exhibit poor color quality and decreased chlorophyll content as compared with the raw material after thermally processed (Adebooye et al, 2008;Turkmen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Others changes in the potato tuber microstructure and texture during cooking have been mainly associated with the gelatinization behavior of starch through the cell wall, and the middle lamellae structural components also play a role (Alvarez, Canet, & Tortosa, 2001). Additionally, cooked potatoes usually exhibit poor color quality compared with fresh tubers because of browning (Turkmen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Texture and color are considered very important parameters in the cooking quality of potato samples, and they may influence consumer purchase of these potato products (Turkmen, Poyrazoglu, Sari, & Velioglu, 2006;Waldron, Smith, Parr, Ng, & Parker, 1997). Changes in the texture are usually dramatic, which is due to the membrane disruption and the associated loss of turgor (Waldron et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Klor ve hidrojen peroksit ile muamele edilmiş örneklerin klorofil içeriği arasındaki farklar çok küçük olduğu için, hidrojen peroksit pazı sanitasyonunda klora alternatif olarak önerilebilir (P<0.05). such as conversion of chlorophyll a and chlorophyll b to their corresponding pheophytins (Turkmen et al 2006). Also, reactions can occur through the removal of phytol group from chlorophylls and pheophytins by the action of enzyme chlorophyllase, resulting in the less stable chlorophyllides and pheophorbides, respectively (Kirca et al 2006).…”
Section: Introductionunclassified
“…Although nearly one-third of chlorophyll a and one-fourth of chlorophyll b reduced at the end of storage period, formation of pheophytins was not observed after any treatments. Pheophytins are the main degradation products of chlorophylls that form mainly during thermal processes (Turkmen et al 2006). Probably, in the degradation of chlorophylls with oxidizing agents such as Cl, O 3 and H 2 O 2 , …”
Section: Comparison Of Susceptibilities Of Chlorophylls Against Diffementioning
confidence: 99%